2016
DOI: 10.1590/s0102-05362016003008
|View full text |Cite
|
Sign up to set email alerts
|

Reação de acessos de jurubeba à murcha bacteriana para uso como porta-enxerto em tomateiro

Abstract: RESUMO A murcha bacteriana, causada pelo patógeno de solo ralstonia solanacearum, é uma séria ameaça à produção de tomate em cultivos sujeitos a alta temperatura e alta umidade. O controle dessa doença é muito difícil e requer várias estratégias, entre as quais a enxertia tem ganhado notoriedade nos últimos anos, em especial após o lançamento de híbridos de porta-enxertos de tomateiro desenvolvidos especiamente para esta finalidade. Embora promovam considerável proteção contra a murcha bacteriana, os porta-enx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 2 publications
0
8
0
2
Order By: Relevance
“…The "vigorous" quality is often reported to show the greatest benefit under sub-optimal growing conditions (Albacete et al 2015b). Tomato scions can also be successfully grafted to rootstocks of other species, including tobacco (Yasinok et al 2009a), eggplant (Oda et al 2005), potato (Peres et al 2005), or various wild Solanum species (e.g., Cortez-Madrigal 2012; Lopes and Mendonça 2016). Many studies have demonstrated that some rootstocks offer other advantages, such as increased tolerance to abiotic stressors including drought (e.g., Cantero-Navarro et al 2016a), salinity (e.g., Rao et al 2013;Albacete et al 2015a), or low temperatures (e.g., Venema et al 2008a).…”
Section: Introductionmentioning
confidence: 99%
“…The "vigorous" quality is often reported to show the greatest benefit under sub-optimal growing conditions (Albacete et al 2015b). Tomato scions can also be successfully grafted to rootstocks of other species, including tobacco (Yasinok et al 2009a), eggplant (Oda et al 2005), potato (Peres et al 2005), or various wild Solanum species (e.g., Cortez-Madrigal 2012; Lopes and Mendonça 2016). Many studies have demonstrated that some rootstocks offer other advantages, such as increased tolerance to abiotic stressors including drought (e.g., Cantero-Navarro et al 2016a), salinity (e.g., Rao et al 2013;Albacete et al 2015a), or low temperatures (e.g., Venema et al 2008a).…”
Section: Introductionmentioning
confidence: 99%
“…The industry of greenhouse vegetables shows similar tendencies across the globe [6]. Watermelon, melon, cucumber, and tomato, among others, are grafted onto rootstocks with tolerance or resistance to soil pathogens [7,8]. The original purpose of plant grafting was to avoid diseases caused by soil parasites and pathogens, such as Verticillium, Fusarium, Phytophthora, Ralstonia, and Nematodos [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…At 50 days after sowing of rootstocks, and 25 days after sowing of the graft (Santa Cruz Kada cultivar), when the plants were grafted from four true leaves, they were processed and grafted using the full slot type fork (Lopes & Mendonça, 2016). The difference between the ages of plants in the moment of grafting occurred due to the difference between the speed of emergence and growth of the evaluated species.…”
Section: Methodsmentioning
confidence: 99%